Hypertriglyceridemia in Critically Ill Patients With SARS-CoV-2 Infection. Issue 6 (June 2022) - El Nekidy, Wasim S.; Shatnawei, Abdullah; Abdelsalam, Manal M.; Hassan, Mariam; Dajani, Ruba Z.; Salem, Nouran; St. John, Terrence J. Lee; Rahman, Nadeem; Hamed, Fadi; Mallat, Jihad
Background: Patients with SARS-CoV-2 infection could develop severe disease requiring critical care admission. Case reports indicated high incidence of hypertriglyceridemia (HTG) in critically ill patients infected with SARS-CoV-2, which might be related to the drugs. Objective: We sought to determine the risk factors associated with HTG in this population and to investigate the relationship between HTG and lipase. Methods: A retrospective observational study was conducted at our hospital between March 1 and June 30, 2020. Patients were included if they were ≥18 years old, admitted to the intensive care unit (ICU), tested positive for SARS-CoV-2, and had triglycerides (TG) checked during their hospital stay. Results: Of the 111 critically ill patients, 103 patients were included. Males comprised 88.3% of the sample. The median TG at baseline was 197.4 (IQR: 139.8-283) mg/dL. The lipase median level at baseline was 23.00 (IQR: 0.00-69.50) IU/L. The results of the mixed-effects logistic regression analysis indicated that patient-level variables, favipiravir use, blood glucose level, and propofol use were significantly associated with HTG. There was no relationship between lipase and TG levels over time. Furthermore, TG concentrations over time showed a similar trend to inflammatory markers. Conclusion and Relevance: The incidence of clinically significant HTG was high and was associated with propofol and favipiravir use. HTG might reflect the high inflammatory state in these patients. Clinicians should look at the full picture before changing therapies based only on HTG. Our findings need to be replicated in a larger prospective study.